2021
DOI: 10.1111/mec.15912
|View full text |Cite
|
Sign up to set email alerts
|

Not just a methane source: Amazonian floodplain sediments harbour a high diversity of methanotrophs with different metabolic capabilities

Abstract: The Amazonian floodplain forests are dynamic ecosystems of great importance for the regional hydrological and biogeochemical cycles and function as a significant CH 4 source contributing to the global carbon balance. Unique geochemical factors may drive the microbial community composition and, consequently, affect CH 4 emissions across floodplain areas. Here, we report the in situ composition of CH 4 cycling microbial communities in Amazonian floodplain sediments. We considered how abiotic factors may affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 77 publications
2
12
0
1
Order By: Relevance
“…The results of these ecological metrics were not generalizable over all soil layers, sampling sites and seasons. Gontijo et al (2021) also observed resistance of methanogenic and methanotrophic microbial communities inhabiting floodplain soils to dramatic environmental changes that occur between seasons in white (Amazonas river) and clear (Tapajós river) water floodplains in the Amazon. However, variations in both occurrence and abundance of methanogenic and methanotrophic microbial taxa between soil layers, FOR and TFS sites, and non-flooded and flooded periods, can be related to metabolic flexibility and physiological adaptations of the microorganisms that may allow them to endure under changing environmental conditions (Ye et al 2018).…”
Section: Ecological Variation In Active Methanogenic and Methanotroph...mentioning
confidence: 81%
“…The results of these ecological metrics were not generalizable over all soil layers, sampling sites and seasons. Gontijo et al (2021) also observed resistance of methanogenic and methanotrophic microbial communities inhabiting floodplain soils to dramatic environmental changes that occur between seasons in white (Amazonas river) and clear (Tapajós river) water floodplains in the Amazon. However, variations in both occurrence and abundance of methanogenic and methanotrophic microbial taxa between soil layers, FOR and TFS sites, and non-flooded and flooded periods, can be related to metabolic flexibility and physiological adaptations of the microorganisms that may allow them to endure under changing environmental conditions (Ye et al 2018).…”
Section: Ecological Variation In Active Methanogenic and Methanotroph...mentioning
confidence: 81%
“…Members of both the Methanoperedenaceae and Methylomirabilaceae families have been previously co-enriched ( Raghoebarsing et al, 2006 ), and in the absence of ammonia, which would inhibit anaerobic ammonia oxidation (anammox) activity and NO 2 – consumption, the dominant microbial consortium in an anaerobic bioreactor fed with CH 4 and NO 3 – was that of the archaeon Candidatus Methanoperdens nitroreducens and the bacterium Candidatus Methylomirabilis oxyfera ( Haroon et al, 2013 ), which were also detected in this floodplain ( Gabriel et al, 2020 ; Bento et al, 2021 ; Gontijo et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…− was that of the archaeon Candidatus Methanoperdens nitroreducens and the bacterium Candidatus Methylomirabilis oxyfera (Haroon et al, 2013), which were also detected in this floodplain (Gabriel et al, 2020;Bento et al, 2021;Gontijo et al, 2021).…”
Section: Ammonia-oxidizing and Nitrogen-dependent Anaerobic Methane-o...mentioning
confidence: 95%
“…Floodplains and wetlands constitute 14% of the total area of the Amazon basin ( 1 ) and are considered the largest natural geographic source of methane (CH 4 ) in the tropics ( 2 ). Therefore, several studies have investigated the CH 4 -producing and -consuming microbial communities in these sediments and their responses to a range of environmental factors using 16S rRNA amplicon sequencing ( 3 5 ). However, their overall microbial taxonomic and functional diversity remains little explored.…”
Section: Announcementmentioning
confidence: 99%
“…Metagenomic libraries were constructed using the NEBNext Ultra II DNA Library Prep Kit for Illumina (New England BioLabs, Inc., Ipswich, MA) and paired-end sequenced (2 × 150 bp) on an Illumina HiSeq 2500 instrument (Illumina, Inc., San Diego, CA) at Novogene Co., Ltd. (Beijing, China). Detailed information about the study sites, sampling, sediment physicochemical properties, and DNA extraction and quantification have been described previously ( 5 ).…”
Section: Announcementmentioning
confidence: 99%